Analysis of current noise pollution regulations in Asunción for the year 2024 (Legal journal - Research in Legal and Social Sciences, 2025)
This scientific article aims to analyze the current regulatory framework governing noise pollution within the city of Asunción, Republic of Paraguay, for the year 2024. The methodological approach is qualitative, conducted through documentary research and at a descriptive level of knowledge. It examines various administrative and criminal regulations, identifying the specific ordinances and laws currently in force pertaining to noise pollution, assessing their efficacy in achieving their stated objectives, and proposing potential solutions to this pervasive issue. Information was extracted from publicly available sources to compile relevant legislation. Furthermore, statistical data regarding complaints registered with the National Police’s 911 Emergency System was obtained. The findings indicate a pressing need to address the issue of noise pollution through a comprehensive approach. This entails strengthening the existing regulatory framework, as well as enhancing enforcement mechanisms and the consistent application of prescribed sanctions, which are currently deemed deficient. The identified shortcomings contribute to a rising number of noise pollution complaints and are associated with detrimental effects on the well-being of the inhabitants of Asunción.
Keywords: noise pollution; contamination; Asunción; regulatory framework; regulations